Galectin-targeting glycocalix[4]arenes can enter the cells - Vlachová, Miluše; Tran, Van Nguyen; Červený, Jakub; Dolníček, František; Petrásková, Lucie; Pelantová, Helena; Kundrát, Ondřej; Cvačka, Josef; Bosáková, Zuzana; Křen, Vladimír; Lhoták, Pavel; Viktorová, Jitka; et al. (Chemical communications (Cambridge, England), 2023)
Elevated levels of galectin-3 are associated with tumorigenesis. Its inhibition with high-affinity carbohydrate ligands opens new therapeutic routes. Targeting of intracellular galectin-3 is challenging for polar inhibitors like carbohydrates. We demonstrate the potential of novel biomedical research tools, glycocalix[4]arenes, to enter epithelial cells, which may allow their interaction with galectin-3.
Keywords: galektin 3; galektiny; sacharidy; Galectins; glykokalyx; buněčná membrána; Galectin 3; Carbohydrates; Glycocalyx; Cell Membrane